The Semiotic Construction of Sars-CoV-2: The Case of The Electron Cryomicroscope - Alessi, Flavio Valerio (E|C, 2023)
The aim of this paper is to analyse the role of the technological devices for Sars CoV 2 molecular structure discovery in cryoelectron microscopy practices. Starting from Bruno Latour's theory of enunciation and insights on techno scientific practices, w e argue that Latour s idea of fabrication of facts can be semiotically framed as a distributed act of enunciation. Specifically, the technological apparatus can be viewed as a mediating instance able to create a commensurability between the virus matter, physically transformed, yet preserved, through the various phases of the protocol, and the experimenters cognition and perception, extended by the device, acting as a diagrammatic and delegate instance. Indeed, on the one hand the cryoelectronic system m anipulates the materic features of the sample as to render it viewable, while, on the other, it produces the interpretants needed by the experimenters to carry out the interpretive process.